Culture is reducing genetic heritability and superseding genetic adaptation. (13th September 2022) - Waring, Timothy M.; Wood, Zachary T.; Xue, Mona J.
Abstract: Uchiyama et al. reveal how group-structured cultural variation influences measurements of trait heritability. We argue that understanding culture's influence on phenotypic heritability can clarify the impact of culture on genetic inheritance, which has implications for long-term gene–culture coevolution. Their analysis may provide guidance for testing our hypothesis that cultural adaptation is superseding genetic adaptation in the long term.